Paediatric brain tumours: The University of Cape Town experience from 1996 - 2017 - Arnold-Day, Christel (Faculty of Health Sciences, 2020)
Brain tumours are the second most common malignancy in children(1) (2), and despite some advancements being made over the last 2 decades, patient outcomes in general remain poor when compared with other childhood cancers. Optimal treatment of children with brain tumours is challenging and expertise and resources are not widely available in South Africa. This is important because the outcomes of children with brain tumours depend critically on the expertise and resources of a multidisciplinary team tasked with their treatment. Despite the importance of paediatric brain tumours though, little is known about childhood brain tumours in South Africa as limited data have been published and there have been no funded studies to support research in this area. In addition, we know very little about the resources available across the country to treat these children. In international centres of excellence the best outcomes are achieved by combining good epidemiological data, strong multidisciplinary teams, centralization or regionalization of services, available resources, and a research foundation. To start, we need to know more about the patients presenting to us with brain tumours. PURPOSE The overall aim of this project was to collect epidemiological data for childhood brain tumours at a tertiary paediatric hospital in South Africa with a dedicated multidisciplinary team. METHODS Study design: A retrospective review of records of patients diagnosed with a primary brain tumour and who presented to Red Cross Children’s Hospital (RCCH) system from 1 January 1996 to 31 December 2017. 2 Patient selection & data collection: Patients were identified by combining databases and admission logs from paediatric neurosurgery, oncology, radiotherapy, histopathology and radiology. Data collected included: age at diagnosis, sex, province of referral, tumour site and diagnosis. RESULTS A total of 554 paediatric patients with primary brain tumours were identified over the study period. Tumours were more common among males (55.4%) and were located in the supratentorial compartment in 52%. The median age at diagnosis was 5.92 years. The commonest tumours were astrocytomas (n=114 patients; 20.3%), followed by medulloblastomas (incl. PNETs) (n=107 patients; 19.1%), and craniopharyngiomas (n=55; 9.8%). As expected, most patients referred and seen at RCCH/GSH were from the expected drainage area in the Western Cape (73%), but a significant number of referrals (27%) were from outside the province referrals, especially in the last 10 years. CONCLUSION Our findings were largely consistent with the published literature in terms of histological diagnosis, sex profile and age ranges for children diagnosed with brain tumours with some small differences possibly related to referral bias. More patients than expected were referred from outside of the province, which emphasizes the need for establishing an ongoing tumour database registry and co-ordinating patient care across institutions. A follow-up study to assess patient management and outcomes is of critical importance to assess resource availability and patient outcomes.